Pretreatment drug resistance in people living with HIV: A large retrospective cohort study in Chongqing, China. (15th March 2022) - Liu, Min; He, Xiao‐Qing; Deng, Ren‐Ni; Tang, Sheng‐Quan; Harypursat, Vijay; Lu, Yan‐Qiu; He, Kun; Huo, Qin; Yang, Hong‐Hong; Liu, Qian; Chen, Yao‐Kai
Abstract: Objectives: The emergence of pretreatment drug resistance (PDR) caused by increased usage of antiretroviral therapy (ART) represents a significant challenge to HIV management. In this study, we evaluated the prevalence of PDR in people living with HIV (PLWH) in Chongqing, China. Methods: We retrospectively collected the data of 1110 ART‐naïve PLWH in Chongqing from January 1, 2018 to June 30, 2021. HIV‐1 genotypes and drug resistance were analyzed using the HIV‐1 pol sequence. Risk factors associated with PDR were evaluated via the logistic regression model. Results: Nine genotypes were detected among 1110 participants, with CRF07_BC (55.68%) being the dominant genotype, followed by CRF01_AE (21.44%), CRF08_BC (14.14%), and other genotypes (8.74%). Of all the participants, 24.14% exhibited drug resistance mutations (DRMs). The predominant DRMs for non‐nucleoside reverse transcriptase inhibitors (NNRTIs) and nucleoside reverse transcriptase inhibitors (NRTIs) were V179D/E/A/DIN (13.60%) and M184V/I (1.44%), respectively, whereas only two major DRMs (M46L and I54L) were identified for protease inhibitors (PIs). The total prevalence of PDR was 10.54%, with 2.43%, 7.66%, and 1.71% participants exhibiting PDR to NRTIs, NNRTIs, and PIs, respectively. Furthermore, female PLWH, delays in ART initiation, and the CRF08_BC genotype were associated with a higher risk of PDR. Conclusions: Our study provides the first large cohort data on the prevalence of PDR in Chongqing, China. HIV‐1 genotypes are diverse and complex, with a moderate level of PDR, which does not reach the threshold for the initiation of a public health response. Nevertheless, continuous surveillance of PDR is both useful and advisable.